Serine and cysteine protease-like genes in the genome of a gall midge and their interactions with host plant genotypes - Chen, Hang; Zhu, Yu Cheng; Whitworth, R. Jeffery; Reese, John C.; Chen, Ming-Shun (My University, 2013)
Proteases play important roles in a wide range of physiological processes in organisms. For plant-feeding insects, digestive proteases are targets for engineering protease inhibitors for pest control. In this study, we identified 105 putative serine- and cysteine-protease genes from the genome of the gall midge Mayetiola destructor (commonly known as Hessian fly), a destructive pest of wheat. Among the genes, 31 encode putative trypsins, 18 encode putative chymotrypsins, seven encode putative cysteine proteases, and the remaining may encode either other proteases or protease homologues. Developmental stage- and tissue-specific expression profiles of the genes encoding putative trypsins, chymotrypsins, and cysteine proteases were determined by quantitative reverse-transcription PCR. Comparative analyses of stage- and tissue-specific expression patterns suggested that several genes are likely to encode digestive proteases in the M. destructor larval gut, including genes encoding putative trypsins MDP3, MDP5, MDP9, MDP24, MDP48, MDP51, MDP57, MDP61, MDP71, and MDP90; genes encoding putative chymotrypsins MDP1, MDP7, MDP8, MDP18, MDP19, and MDP20; and genes encoding putative cysteine proteases MDP95 and MDP104. The expression of some protease genes was affected by plant genotypes. Genes encoding trypsins MDP3, MDP9, and MPD23, chymotrypsins MDP20 and MDP21, and cysteine proteases MDP99 and MDP104 were upregulated in M. destructor larvae feeding in resistant plants, whereas genes encoding trypsins MDP12, MDP24, and MDP33, and chymotrypsins MDP8, MDP15, and MDP16 were downregulated in M. destructor larvae feeding in resistant plants. This study provides a foundation for further comparative studies on proteases in different insects, and further characterization of M. destructor digestive proteases and their interactions with host plants, as well as potential targets for transgenic wheat plants.
Keywords: Hessian fly genome; Mayetiola destructor; Serine protease; Cysteine protease; Gut proteinases